Structure, morphology and hydrogen storage kinetics of nanocomposite MgH2/10 wt% ZrNi5 powders. (March 2017) - El-Eskandarany, M. Sherif; Shaban, Ehab; Al-Matrouk, Hasan; Behbehani, Montaha; Alkandary, Abdullah; Aldakheel, Fahad; Ali, Naser; Ahmed, S.A.
Abstract: Reactive ball milling was employed to synthesize nanocrystalline MgH2 powders under a hydrogen gas pressure of 50 bar for 200 h, using a high-energy ball milling. In part to improve the hydrogen absorption/desorption kinetics of as-prepared MgH2, the powders were doped with 10 wt% ZrNi5 powders and then mechanically ball milled for 50 h. The nanocomposite powders possessed superior hydrogenation/dehydrogenation properties, indexed the short time required for achieving a complete hydrogen absorption (1 min) and desorption (10–12 min) of 5.3 wt% H2 at 275 °C. van't Hoff approach was used to calculate the enthalpy of hydrogenation and dehydrogenation for MgH2 phase in the nanocomposite powders and found to be −72.85 and 77.07 kJ/mol, respectively. Moreover, this nanocomposite system possessed excellent hydrogen absorption/desorption cyclability of 600 complete cycles, conducted at 275 °C with a cyclic-life-time reached to 568 h without serious kinetics degradation. Graphical abstract: Highlights: Room-temperature synthesizing of nanocomposite MgH2 /10 wt% ZrNi5, using high-energy ball milling. ZrNi5 nanocatalysts leading to decrease the activation energy of MgH2 . The hydrogenation/dehydrogenation kinetics were significantly improved. The role and effect of ZrNi5 grain size on modifying the behavior of MgH2 . Effect of doping MgH2 with ZrNi5 on the enthalpy of hydrogenation/dehydrogenation.